Interleukin-17 and myeloperoxidase levels in patients with non-alcoholic fatty liver disease and effect of disease severity on blood counts and liver enzymes - Mamoona Nazir; Ahmer Ijaz; Nayab Imtiaz; Muhammad Yasir Khan; Gulab Fatima Rani (Khyber Medical University Journal)
Objectives: To compare the circulating levels of interleukin-17 (IL-17) and myeloperoxidase (MPO) in non-alcoholic fatty liver disease (NAFLD) patients and healthy controls, and to assess the impact of disease severity on blood counts and liver enzyme levels, exploring their potential as early markers.